Evaluasi Kesesuaian Lahan Untuk Pengembangan Kelapa Babasal (Cocos nucifera) Di Kecamatan Batui Kabupaten Banggai - Hidayat Arismunandar Katili (Universitas 17 Agustus 1945 Samarinda, 2021)
Evaluation of Land Suitability for the Development of Babasal Coconut (Cocos nucifera) in Batui District, Banggai Regency. This study aims to determine land suitability and limiting factors as well as processing efforts in the development of Babasal Coconut (Coconus nucifera) in Batui District. This study lasted for 3 months (July-September 2020) using the parametric approach method of Khiddir's (1986) square root land index. The results showed that the actual land suitability class in Batui District SPL 1, SPL 2, SPL 3, SPL 4, SPL 5, SPL 6, SPL 7, SPL 8, SPL 9 were S3 (marginal) while the limiting factors were texture, slope, flood hazard and N-total. Furthermore, for improvement efforts are moderate to high level management by fertilizing, making terraces, planting parallel to contours, planting ground covers, constructing embankments and constructing drainage channels. The allocation direction for Babasal coconut (Coconus nucifera) development in Batui District with potential suitability class SPL 3 is classified as S1 criteria (very suitable) with an area (3731.16 ha). Furthermore, at SPL 1, SPL 2, SPL 4, SPL 5, SPL 6, SPL 7, SPL 8 and SPL 9 with S3 criteria (marginal) with an area (21288.21 ha) while the limiting factor for potential land suitability in Batui District is the texture content criteria are rather rough and cannot be repaired